2011
DOI: 10.1111/j.1478-3231.2011.02561.x
|View full text |Cite
|
Sign up to set email alerts
|

NOD2 gene variants are a risk factor for culture‐positive spontaneous bacterial peritonitis and monomicrobial bacterascites in cirrhosis

Abstract: NOD2 variants increase the risk for culture-positive SBP and bacterascites in cirrhosis and may affect survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 34 publications
4
50
1
5
Order By: Relevance
“…Of note, carriers of NOD2 risk alleles showed a significantly (p = 0.007) reduced mean survival time (274 days) in comparison to patients without mutations (395 days) [16] . This association was replicated for culture-positive SBP; an interesting finding in this study was that patients with NOD2 variants presented more often with variceal bleeding and hepatocellular carcinoma [17] .…”
Section: Liver Cirrhosissupporting
confidence: 60%
“…Of note, carriers of NOD2 risk alleles showed a significantly (p = 0.007) reduced mean survival time (274 days) in comparison to patients without mutations (395 days) [16] . This association was replicated for culture-positive SBP; an interesting finding in this study was that patients with NOD2 variants presented more often with variceal bleeding and hepatocellular carcinoma [17] .…”
Section: Liver Cirrhosissupporting
confidence: 60%
“…3 The expression of NF-jB was increased after 72 h stimulation by MDP and Af conidia; the effect was interrupted by RNA interference of NOD2. *p \ 0.05 versus control (CON), # p \ 0.05 versus without RNAi factors of bacterial infection and are associated with early mortality in sepsis patients [13,14]. Meanwhile, the effect of NOD2 in detecting microorganisms and induction of innate immune response was shown in Toxoplasma gondii [15], virals [16], Streptococcus pneumonia, Mycobacterium tuberculosis, Staphylococcus aureus [17,18], Listeria monocytogenes [19], and recently in the intracellular pathogens Legionella pneumophila [20] and Chlamydophila pneumonia [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, essentially all animal models of intestinal fibrosis appear to be dependent on the presence of a microflora to initiate or perpetuate gut inflammation and fibrosis [25]. Although direct evidence about the innate immunity gene variants in liver fibrosis is lacking, several studies have shown that NOD2 is associated with the increased mortality in nonalcoholic liver transplant patients [30] or the increased risk of spontaneous bacterial peritonitis in patients with liver cirrhosis [31,32]. …”
Section: Innate Immunitymentioning
confidence: 99%